La frontera en la comunidad imaginada del siglo XIX - Enrique Rajchenberg S. (El Colegio de la Frontera Norte, 2007)
The recent studies that focused on the historical process of national identitys construction in Mexico have not emphasized enough one approach: the social representation of territory. This paper explores this topic in the XIXth century Mexico intending to demonstrate how the sense of belonging and the attachment to motherland reduce the imagined nation to the limits of the central lands, the ancient Mesoamerica, excluding of the national social representations the vast north through symbolic stigmatization contrasting with the core (centre) of the country full of geosymbols and posed as a privileged source for historical memory.